2017
DOI: 10.1002/fam.2491
|View full text |Cite
|
Sign up to set email alerts
|

Insightful investigation of smoke suppression behavior and mechanism of polystyrene with ferrocene: An important role of intermediate smoke

Abstract: Summary Aiming to investigate the smoke suppression mechanism of ferrocene in model polystyrene (PS) during combustion, we exploited the vapor‐phase and condensed‐phase behaviors. Cone calorimeter testing result showed that 3 wt% ferrocene imparted PS with 56.9% reduction in total smoke production. The analysis of the char after cone calorimeter testing demonstrated that the condensed‐phase smoke suppression mechanism was weak owing to the absence of charring behavior. The vapor‐phase mechanism was focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…At the loading of 1 wt%, a relatively small fraction of iron derivatives did not influence the thermal stability visibly. In contrast, the loadings of 2 wt% and 3 wt% generated relatively high fraction of iron derivative, resulting in the earlier catalytic degradation of PS [26]. The similar case was observed in T max .…”
Section: Thermal Degradation Of Ps Compositessupporting
confidence: 52%
“…At the loading of 1 wt%, a relatively small fraction of iron derivatives did not influence the thermal stability visibly. In contrast, the loadings of 2 wt% and 3 wt% generated relatively high fraction of iron derivative, resulting in the earlier catalytic degradation of PS [26]. The similar case was observed in T max .…”
Section: Thermal Degradation Of Ps Compositessupporting
confidence: 52%
“…This test indicated that KC–Fe was thermally decomposed in the condensed phase and that the iron oxide formed by thermal decomposition was stored in the residual char of the flame-retardant EP. The iron oxide can adsorb and catalyze the combustion of small molecular substances to form a stable char layer structure, thereby achieving a smoke suppressing effect [12,41].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, it has been found that the addition of metal oxides and flame-retardants simultaneously into polymer composites can not only significantly improve the flame-retardant properties of the composites, but also improve their smoke suppression properties [12,13,14,15,16]. Recently, it was reported that Fe 2 O 3 readily forms a stable Fe–O–P cross-linked network structure with phosphoric acid, thereby increasing the char residue for a flame-retardant coating at high a temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of fire fatalities are caused by the lethal atmosphere resulting from the combustion of polymers. 30,31 Therefore, the reduction of smoke and toxic gases will be beneficial to the fire rescuer.…”
Section: Smoke Suppression Of the Eva-fr Compositesmentioning
confidence: 99%